A study of pattern of self medication practices among medical students in government medical college of Madhya Pradesh, India - Marko, Shashi; Alawa, Mahesh Chandra (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Self medication practice has tremendously increased in the society that leads to unwanted consequences such as drug resistance and adverse drug reactions. The objective of this study was to evaluate the self-medication practices among the second year medical students of Government Medical College, Sagar. Methods: It was a questionnaire based descriptive study. A prevalidated questionnaire were given to the second year medical students. Data were analyzed using excel sheet and result were expressed as counts and percentages. Results: Males outnumber females in this study, 40 versus 35. The most common indication for which self medication was opted was cold and cough. The most common source of information used by the respondent were text book (61.29%) and pharmacist (45.16%). The attitude was positive towards self medication and favored self-medication saying that it was acceptable. Drug groups commonly used for self-medication included analgesics 77.41% and antipyuretics 50% and anta-acids 48.38%. Among reasons for seeking self-medication, 79.03% felt that their illness was minor while 64.51% preferred as it is due to previous experience. Conclusions: This study shows that self-medication is widely practiced among second year medical students of this institution. There is intense need to make them aware about the pros and cons of self-medication in order to ensure safe usage of drugs.